ЎЗБЕК МАРОСИМ ФОЛЬКЛОРИДА ТУХУМ БИЛАН БОҒЛИҚ МАГИК ҚАРАШЛАР - Худайқулова, Л.А. (SCIENCE and SOCIETY, 2021)
This article discusses the role of the egg in Uzbek ritual folklore and related magical views.